The effect of cancer treatment summaries on patient-centered communication and quality of care for cancer survivors: A pooled cross-sectional HINTS analysis. Issue 2 (February 2020) - Swoboda, Christine M.; Fareed, Naleef; Walker, Daniel M.; Huerta, Timothy R.
Highlights: Fewer than half of cancer patients receive treatment summaries. Treatment summaries help improve some domains of patient-centered communication. Treatment summaries alone may not improve quality of care. Abstract: Objective: Provision of cancer treatment summaries to patients is recommended to improve patient-centered communication (PCC). The objective of this study is to assess relationships between cancer treatment summary receipt, PCC, and quality of care (QOC). Methods: Linear and logistic regression of cross-sectional data from the Health Information National Trends Survey (HINTS) was conducted using data from years 2012, 2014, and 2017. The independent variable was receipt of treatment summary; the dependent variables were overall PCC score, six domains of PCC, and QOC. Results: In the pooled sample, 36.9% of patients with cancer treatment history reported receiving a treatment summary. There was a significant positive association between overall PCC score and treatment summary receipt, and higher odds of high scores for the PCC domains "responding to emotions" and "managing uncertainty." We did not observe significant associations between treatment summary receipt and other PCC domains or QOC. Conclusion: Providing patients cancer treatment summaries may improve PCC, but fewer than half of patients reported receiving one of these summaries. Practice Implications: Providing cancer treatment summaries is important, however, providing them without engaging in additional communication may be insufficient to improve all patient-centered care domains or quality of care.